Beyond the Purchase: Unpacking Consumer Behaviour and Its Environmental Impact - Sripathi, Dr. Madhavi; Rayapudi Harsha Sai; Syed Luqhman; Borra Sasi Kanth (Journal of Advanced Research in Operational and Marketing Management, 2025)
This research, "Beyond the Purchase: Unpacking Consumer Behaviour and Its Environmental Impact," investigates Indian consumer post-consumption activity—namely how they are eliminating packaging waste via reuse, recycling, or dumping. Focused on Andhra Pradesh's Krishna and Guntur districts, the research examines how knowledge, attitudes, feelings, and infrastructural determinants drive recycling behaviour. Conclusion : From a cross-sectional survey supplemented with secondary data extracted from neighbourhood and government records, the article finds discernible trends in packaging waste disposal practices. The findings show although the majority of individuals are sensitive to environmental impacts and responsive to behaving sustainably, an awareness–behaviour gap exists—triggered by poor infrastructure, information shortcomings, and being price-sensitive. The research focuses on policy adjustment convergence, behavioural economics, and improved recycling design to smooth the transition towards circular economy trends. The paper concludes that Indian post-consumption buying behaviour has a huge influence on environmental conditions and that good communication, emotional connection, and infrastructure development are necessary to bridge the intention–action gap.